The Ins and Outs of Myeloid Cells in Atherosclerosis - Schumski, Ariane (J Innate Immun, 2018)
Atherosclerosis is a chronic inflammation of the arterial vessel wall that arises from an imbalanced lipid metabolism. A growing body of literature describes leukocyte recruitment as a critical step in the initiation and progression of lesion development. By contrast, the role of leukocytes during plaque regression has been described in less detail. Leukocyte egress might be an important step to resolving chronic inflammation and therefore it may be a promising target for limiting advanced lesion development. This review aims to summarize our current knowledge of leukocyte recruitment to the arterial vessel wall. We will discuss mechanisms of leukocyte egress from the lesion site, as well as potential therapeutic strategies to promote atherosclerotic regression.